A dietary pattern derived using B-vitamins and its relationship with vascular markers over the life course. Issue 3 (June 2019) - Maddock, Jane; Ambrosini, Gina L.; Griffin, Julian L.; West, James A.; Wong, Andrew; Hardy, Rebecca; Ray, Sumantra
Summary: Background: Diet may influence vascular function through elevated homocysteine (Hcy) concentrations. However the relationship between dietary patterns (DP), characterised by Hcy and its associated nutrients is unknown. Objective: To identify a DP characterised by plasma Hcy, dietary folate and dietary vitamin B12, and examine its associations with two markers of vascular function: carotid intima-media thickness (cIMT) and pulse wave velocity (PWV). Methods: 1562 participants of the MRC National Survey of Health and Development (NSHD), a British birth cohort, with dietary data measured at least once between 36 and 60–64 years, and cIMT or PWV measured at 60–64 years were included. DPs were derived using reduced rank regression with three intermediate variables: 1) plasma Hcy (μmol/L) 2) folate intake (μg/1000 kcal) 3) vitamin B12 intake (μg/1000 kcal). Multiple regression models assessed associations between the derived DP z-scores and vascular function adjusting for dietary misreporting, socioeconomic position, BMI, smoking, physical activity and diabetes. Results: A DP explaining the highest amount of shared variation (4.5%) in plasma Hcy, dietary folate and dietary vitamin B12 highly correlated with folate ( r  = 0.96), moderately correlated with vitamin B12 ( r  = 0.27), and weakly correlated with Hcy ( r  = 0.10). This "high B-vitamin" DP (including folate) was characterised by high intakes of vegetables, fruit and low fibre breakfast cereal, and low intakes of processed meat, white bread, sugar and preserves. No associations were observed between DP z-scores and vascular function at any time point following adjustment for covariates. Conclusion: This study explored a specific hypothesised pathway linking diet to vascular function. Although we found no consistent evidence for an association between a high B-vitamin DP and vascular function, we did observe an association with CRP and triglycerides in secondary analyses. Further analyses using strongly correlated and biologically relevant intermediate variables are required to refine investigations into diet and CVD in longitudinal cohort data.